Petersen Family Host Private Reception for Mayor of Djambul - Watkins, Howard::::::::: (1989)
?, Mayor of Djambul speaking, Chris Petersen, Walt Loscutoff, Mayor of Fresno Karen Humphrey and Susan Loscutoff